Ab initio study of the effect of hydrogen passivation on boron-oxygen-carbon related defect complexes in silicon. (May 2020) - Abdurrazaq, A.; Raji, Abdulrafiu T.; Meyer, Walter E.
Abstract: We present hybrid density functional theory (DFT) study of defect complexes formed by oxygen, boron and carbon, in ion-implanted and electron-irradiated Czrolaski (CZ) silicon containing boron. The effect of hydrogen passivation on the defect complexes is also studied. The defects considered are the interstitial boron-interstital oxygen (B i O i ) complex as well as interstitial boron-substitutional carbon (B i C s ) complex, which are found in ion-implanted Czochralski silicon. Other defect complexes which are found in electron-irradiated CZ silicon and have been studied are the interstitial boron (B i ), substitutional boron-interstitial oxygen (B s O i ), substitutional boron-interstitial boron (B s B i ), interstitial boron-interstitial oxygen dimer (B i O2 i ), and substitutional boron-interstitial oxygen dimer (B s O2 i ). We found the defects to be stable in neutral charge state with the stability of the B i, B i O i, B s B i, B i O2 i and B s O2 i increasing after hydrogen passivation. However, the stability of B s O i and B i C s defect complexes decreases after the hydrogen passivation. For the B s B i defect complex in particular, a deep donor level appeared after hydrogen passivation. Furthermore, we found a shift in the charge state transition levels in to the valence band for the donor levels, and a shift in to the conduction band for the acceptor levels for all the defects after hydrogen passivation. We compare our results with available theoretical and experimental studies.